Implementasi Penyusunan Laporan Keuangan Berdasarkan Isak No 35 (Studi Kasus Panti Asuhan Yasibu Arjowinangun Malang) - Ridwan Setyono; Khojanah Hasan; Dwi Aggarani (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
Non-profit organisations are organisations that do not have commercial objectives in their operations and do not seek to make a profit. As a public sector organisation engaged in social work, orphanages receive funds from donors, so non-profit organisations need to prepare financial statements to fulfil their obligations to internal and external parties who require their financial reports. This study aims to examine the financial statements presented by the Yasibu Arjowinangun Malang Orphanage and then compile the financial statements of the Yasibu Arjowinangun Malang Orphanage based on the applicable Financial Accounting Standards, namely ISAK No. 35. This study is a qualitative descriptive study. The study uses data on cash receipts and cash disbursements in 2024. The data used are primary and secondary data obtained through documentation and interviews. The results of this study present the financial statements of the Yasibu Arjowinangun Malang Orphanage in accordance with ISAK No. 35, consisting of: Comprehensive Income Statement, Statement of Changes in Net Assets, Statement of Financial Position, Cash Flow Statement, and Notes to the Financial Statements.